2012
DOI: 10.1007/s00134-012-2500-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of end-of-life decisions in two Tunisian intensive care units: the role of culture and intensivists’ training

Abstract: Withholding and withdrawing life support are common in medical and surgical ICUs of a Tunisian hospital. Withholding is more frequent than withdrawing life support. These decisions appear to be effected by functional status and underlying conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Some studies suggest that this variation originates from institutional factors [10,[16][17][18][19][20][21], physician factors [10,[22][23][24][25], and religion/geographic factors [25][26][27]. Variation in earlier studies was not only found between countries, but also within countries [10,[16][17][18][28][29][30][31][32][33][34], and even within the same department [23]. This could indicate that cultural or regional differences are not the sole trigger of variation in the occurrence of WLSM.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies suggest that this variation originates from institutional factors [10,[16][17][18][19][20][21], physician factors [10,[22][23][24][25], and religion/geographic factors [25][26][27]. Variation in earlier studies was not only found between countries, but also within countries [10,[16][17][18][28][29][30][31][32][33][34], and even within the same department [23]. This could indicate that cultural or regional differences are not the sole trigger of variation in the occurrence of WLSM.…”
Section: Discussionmentioning
confidence: 96%
“…When compared with patients with other chronic diseases, cancer patients usually have to experience much more psychological stress and economic burden in addition to physical sufferings. It was reported that critically ill patients with malignancy or ultimately fatal underlying diseases were more likely to have their life-sustaining therapy withheld or withdrawn than those without malignancy or fatal diseases [15][16]. A study of a specialized cancer center in Jordan demonstrated a high proportion (48.6%) of adult cancer patients making decisions to withhold or withdraw life support measures [17], which was even higher than the result of our center.…”
Section: Discussionmentioning
confidence: 59%
“…Indian nurses felt it correct to continue hydration and feeding until death, but not to initiate invasive procedures [35], with a high threshold for treatment initiation has been found [36]. Such findings are mirrored in studies in other countries such as Egypt and Tunisia [31,37], and a study in Pakistan found that 16% would not withdraw life support under any circumstances [29].…”
Section: Withholding Withdrawing Treatment Futility and Legal Issuesmentioning
confidence: 99%